ByzRev 04.2022.005: Roland Betancourt, Performing the Gospels in Byzantium: Sight, Sound, and Space in the Divine Liturgy.: Cambridge – New York: Cambridge University Press, 2021. - Parpulov, Georgi (The Byzantine Review, 2022)
Roland Betancourt, Performing the Gospels in Byzantium: Sight, Sound, and Space in the Divine Liturgy. Cambridge – New York: Cambridge University Press, 2021. xxii, 330 pp. with 127 ill. – ISBN 978-11-0849139-6 ( 130.00)